2010
DOI: 10.1016/j.neuroscience.2010.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of nerve sprouting and neuroma formation markedly attenuates the development of late stage cancer pain

Abstract: For many patients, pain is the first sign of cancer and, while pain can be present at any time, the frequency and intensity of pain tend to increase with advancing stages of the disease. Thus, between 75 and 90% of patients with metastatic or advanced-stage cancer will experience significant cancer-induced pain. One major unanswered question is why cancer pain increases and frequently becomes more difficult to fully control with disease progression. To gain insight into this question we used a mouse model of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
186
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(204 citation statements)
references
References 58 publications
(85 reference statements)
11
186
0
7
Order By: Relevance
“…The potential role of sensory neurons and their association with sympathetic and parasympathetic neurons remains to be defined. Mantyh and colleagues have documented in detail that autonomic nerves, especially sympathetic postganglionic fibers, are affected in cancer progression (5,(54)(55)(56). Moreover, both sympathetic and parasympathetic neurons release molecules that can activate sensory neurons; sympathetic postganglionic neurons release three molecules of ATP for every molecule of norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of sensory neurons and their association with sympathetic and parasympathetic neurons remains to be defined. Mantyh and colleagues have documented in detail that autonomic nerves, especially sympathetic postganglionic fibers, are affected in cancer progression (5,(54)(55)(56). Moreover, both sympathetic and parasympathetic neurons release molecules that can activate sensory neurons; sympathetic postganglionic neurons release three molecules of ATP for every molecule of norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-NGF therapy is remarkably effective in a broad variety of pain conditions ranging from muscle pain to bone cancer pain (Mantyh et al, 2010(Mantyh et al, , 2010Jimenez-Andrade et al, 2011). This remarkable efficacy of anti-NGF probably arises through the broad range of molecular events that are set into motion by elevated NGF levels in a variety of different tissues.…”
Section: The Ngf Nexus Of Painmentioning
confidence: 99%
“…Furthermore, studies have shown that cancer cells in the bone induce a highly disorganized sprouting of sensory and sympathetic ibers, leading to the formation of small neuromas. These disorganized bundles of nerve ibers are thought to contribute to episodes of breakthrough pain or even movement-induced pain [64,65]. In addition to changes in nerve ibers, bone tumors in mice have also been shown to be associated with changes in both blood vessels and lymphatics, which may facilitate metastasis and which, interestingly, can be altered by acupuncture treatment [66].…”
Section: Peripheral Mechanismsmentioning
confidence: 99%